SAT0386 The structural basis of MRI bone erosions- an assessment by micro computed tomography. (23rd January 2014) - Albrecht, A.; Finzel, S.; Rech, J.; Englbrecht, M.; Schett, G.
Abstract : Background: Micro-CT (μCT) allows to directly measure the volume of individual erosions and thus exactly defines the extent of structural damage. Based on our experience with high resolution μCT scanning we were interested to validate the nature of MRI bone erosions. (1) Objectives: To determine whether erosions appearing in magnetic resonance imaging (MRI) in patients with rheumatoid arthritis (RA) represent true erosions. Methods: 50 RA patients received 1, 5 Tesla MRI as well as micro computed tomography (μCT) of the dominant hand. Erosion counts were assessed coronal T1 weighted MRI sections and coronal as well as transversal μCT sections of the metacarpophalangeal (MCP) joints II-IV. Extent of erosions was assessed by RAMRIS erosion score (MRI) and by 3-dimensional assessment of erosion volume (μCT). (2) Results: 111 erosions were found in the MRI and 137 in the μCT. 32 false negative lesions (μCT positive, MRI negative) were found, all of which were very small lesions with a volume of less than 10mm 3 . Only 6 results were false positive (μCT negative, MRI positive). RAMRIS erosion scores were strongly correlated to erosion volumes in the μCT (Pearson r =0.514, p<0.001) (see Fig. 1 for details). Mean RAMRIS scores were below 1 with erosion volumes up to 1.5 mm 3, below 2 with erosion volumes up to 20 mm 3 and over 2 with volumes of more than 20 mm 3 . Conclusions: MRI erosions are generally based on true cortical breaks as shown by μCT. MRI is sensitive to detect bone erosions and only very small lesions escape detection. Moreover, RAMRIS erosion scores are closely linked to the absolute size of bone erosions in the μCT. References: Stach CM, Bauerle M, Englbrecht M, Kronke G, Engelke K, Manger B, et al. Periarticular bone structure in rheumatoid arthritis patients and healthy individuals assessed by high-resolution computed tomography. Arthritis and rheumatism. 2010;62(2):330-9. Conaghan P, Bird P, Ejbjerg B, O'Connor P, Peterfy C, McQueen F, et al. The EULAR-OMERACT rheumatoid arthritis MRI reference image atlas: the metacarpophalangeal joints. Annals of the rheumatic diseases. 2005;64 Suppl 1:i11-21. Disclosure of Interest: None Declared